The effectiveness of the operation of the information and communication system: student satisfaction measurement (Training and Practice : Journal of Educational Sciences, 2018)
In our study we examine the information and communication system of the Hungarian Language Teacher Training Faculty of the University of Novi Sad in the light of the students’ satisfaction. A total of 1019 tutor and teacher trainees were satisfied with the communication system between teachers and students, with the available resources of information, and with the operation and efficiency of traditional and advanced teaching tools. On the basis of the results, students are satisfied with the availability of compulsory and recommended literature, and the use of modern teaching materials for all of the subject groups that were studied. They consider the resources of available information at the university, the library resources, and the electronic tools to be adequate. They are also satisfied with the possibilities to take part in consultations.